2007
DOI: 10.1097/mlg.0b013e3180caa162
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Hearing Disability After Acoustic Neuroma Removal

Abstract: This study demonstrates that, compared with a control population, these patients experience a significant range of auditory disabilities. It is important that clinicians be aware of the impact of such a profound unilateral HL and its potential to affect daily life. Patient counseling prior to surgery is essential, especially in patients whose loss of binaural hearing could constitute a major disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 15 publications
3
66
1
1
Order By: Relevance
“…Based on the SSQ total subscale scores, more than 75% of the AHL population experienced a hearing disability. A review of the literature Douglas et al, 2007] suggests similar results. For the remaining 25% of our AHL cohort, closer approximations to scores achieved for the NHL were observed.…”
Section: Resultssupporting
confidence: 64%
“…Based on the SSQ total subscale scores, more than 75% of the AHL population experienced a hearing disability. A review of the literature Douglas et al, 2007] suggests similar results. For the remaining 25% of our AHL cohort, closer approximations to scores achieved for the NHL were observed.…”
Section: Resultssupporting
confidence: 64%
“…The only subscales that do not indicate a benefit are speech in quiet and identification of sound and objects. Previous investigations have demonstrated the challenges associated with monaural hearing using the SSQ pragmatic subscales [Douglas et al, 2007;Dwyer et al, 2014]. Douglas et al [2007] reported poorer speech perception in multiple speech-stream processing and switching, localization, and listening effort in patients with substantial UHL resulting from acoustic neuroma removal as compared to a NH cohort.…”
Section: Pragmatic Subscalesmentioning
confidence: 99%
“…While audiological assessment of hearing intervention tends to focus on behavioral measures, such as speech perception, these measures do not capture all of the functional benefits that CI recipients experience in real-world listening conditions. For instance, patients with UHL may present with high levels of speech perception in quiet due to the NH ear and yet report poor speech and spatial hearing as compared to their NH peers [Douglas et al, 2007;Wie et al, 2010]. Inclusion of quality of life measures in addition to behavioral measures may provide a more thorough understanding of whether cochlear implantation is an effective treatment option for substantial UHL.…”
Section: Introductionmentioning
confidence: 99%
“…Single-sided deafness (SSD) affects the quality of life of patients, since they experience discomfort in difficult situations such as hearing in noise or sound localization [Douglas et al, 2007]. The loss of hearing in one ear suppresses the interaural time and sound level differences that are responsible for localization [Kitterick et al, 2014].…”
Section: Introductionmentioning
confidence: 99%